Strategi Manajemen Perpustakaan MAN Asahan dalam Meraih Peringkat Terbaik I Tingkat SLTA Se-Sumatera Utara Tahun 2021 - Alamsyah, Rizky; Titin Sumanti, Solihah; Ismail, Ismail (Comit: Communication, Information and Technology Journal, 2024)
A good library that is able to provide the right information for users,it’s all based on good management as well. The function of managements is so that goals can run in an orderly manner as expected. In this study using field research with a qualitative approach. Techniques used for data collection using observation, interviews and documentation. Meanwhile, the data analysis technique went throught the stages of data reduction, data presentation and verification. In this study, researchers want to examine the MAN Asahan library in management functions, namely planning, organization, actuacting, controlling and evaluation. The result of this study are that the MAN Asahan library has three planning programs, namely long-term, medium-term and short-term programs. Which the task is carried out or carried out in accordance with the duties of the libraries who work in accordance with their respective fields. The shortage of the MAN Asahan library is still the lack of the number of collection and the facilities of the MAN Asahan library are still many that are not suitable for users. Keywords: Library Management, Management Function